Willingness to pay for the preservation of urban green space in Indonesia - Idris Idris; Mohammad Enamul Hoque; Perengki Susanto (Cogent Economics & Finance, 2022)
Padang has just begun to build an urban green space to increase the quality of the urban environment and provide recreational opportunities to residents. In such cases, a well-informed professional management plan needs to be formulated to preserve a better environment. Therefore, this study seeks to determine the visitors' willingness to pay for the preservation of urban green space. This study was carried out at the Urban green space of Imam Bonjol Park Padang using a survey approach, and the respondents were chosen using the purposive technique. The logistic regression shows that the willingness to pay for the urban green space is affected by the visitors' perception of Imam Bonjol Park, the knowledge of functions, and marital status. The empirical results show that income, family dependents, and park-related factors are insignificant in influencing willingness to pay for the urban green space. Using the Contingency Valuation Method, this study discovered that most visitors are willing to pay some amount for environmental preservation, and the estimated amount is IDR. 4,877. The empirical results have a few practical implications. As a result, this study suggests launching awareness-raising programs.
Keywords: 330; Urban green space; willingness to pay; contingency valuation method